Study on the Dynamic Magnification Effect of Structure Stiffness Based on the Gust Coupling Analysis of Civil Aircraft - Yingying Liu; Kaiping Yu; Jinze Li (Aerospace)
Regarding the dynamic magnification effect of structure stiffness on the gust analysis of civil aircraft, the following three methods are presented: rigid modes analysis, secondary processing based on elastic modes, and analysis with enlarged stiffness. These methods provide consistent gust load and address the challenge of extracting internal gust loads of rigid aircraft. The coupling resonant effects of the inertial force, the aerodynamic force, and the gust-induced aerodynamic force at different frequencies are examined. The response of flexible aircraft is nonlinearly related to frequency. It exhibits a significant increase in the inertial force and the aerodynamic force at higher frequencies, while a quasi-rigid response at very low frequencies shows the importance of sufficient analysis time. In addition, compared with rigid aircraft, flexible aircraft experiences a delay in the occurrence of extreme gust loads with the delay interval proportional to the frequency. The maximum gust load of flexible aircraft under a certain range of frequencies exceeds that of rigid aircraft, although this is not necessarily the case at the specific frequency. The dynamic magnification factor is 1.25 for the model in this study, which is almost constant and reaches its maximum value together with the gust loads when the frequency coincides with the frequency of the first bending mode.